Interactions between genetic predisposition and environmental toxicants for development of lung cancer - El-Zein, Randa; Conforti-Froes, Nivea [UNESP]; Au, William W. (My University, 1997)
Significant interindividual variations in health outcome may be caused by the inheritance of variant polymorphic genes, such as CYP2D6 and CYP2E1 for activation, and GSTM1 and GSTT1 for detoxification of chemicals. However, mechanistic studies linking the inheritance of predisposing genes with genotoxic effects towards cancer have yet to be systematically conducted. We have studied 54 lung cancer patients and 50 matched normal controls, who have been cigarette smokers, to elucidate the role of polymorphic genes in cancer. Our data indicates that the inheritance of unfavorable CYP2D6, CYP2E1, and GSTT1 genes is strongly correlated with the smoking-related lung cancer. For heavy cigarette smokers (>30 pack-years), the smoking habit is the strongest predictor of lung cancer risk irrespective of the inheritance of unfavorable metabolizing genes. For moderate to light smokers (<30 pack-years) the genetic predisposition plays an important role for the risk (odds ratio = 3.46; 95% CL = 0.46-40.2). Using a subgroup of the study population, we observed that cigarette smokers having the defective GST genes have significantly more chromosome aberrations as determined by the fluorescence-in-situ-hybridization (FISH) technique than smokers with the normal GST genes (P < 0.001). In conclusion, our study provides data to indicate that individuals who have inherited unfavorable metabolizing genes have increased body burden of toxicants to cause increased genetic damage and to have increased risk for cancer. Studies like ours can be used to understand the basis for interindividual variatons in cancer outcome, to identify high risk individuals and to assess health risk.
Keywords: Environmental toxicants; Lung cancer risk; Polymorphic genes